The Variations of Saridin Story According to The Reception of Kethoprak Viewer (Seloka: Jurnal Pendidikan Bahasa dan Sastra Indonesia, 2019)
The story of Syeh Jangkung or Saridin in various forms and versions producing to the novelty or innovation through both spoken from mouth to mouth, kethoprak, and written stories. This study was intended to explore variations of Saridin's stories that are presented in the midst of society. The data sources were four documnet and then was processed using a qualitative narrative analysis method. The result was based on the theme, Serat Seh Jangkung and Saridin Andum Waris which has the same story idea about the story of Nomads and the journey of Seh Jangkung in several areas. The journey taken not only throughout Java, but also in Sumatra and Rome. In Saridin Mokong, the figure of Saridin's wife, is a character who represents a story that struggles to maintain the dignity and prestige of Javanese women. Then, the theme of Syeh Jangkung Andum Waris is about Saridin's patience in facing trials. Diversity is also found in the prologues, acts and scenes, characters and characterizations, settings, plots, and epilogues. Overall, Saridin's story was not only written and enjoyed by the public of readers or listeners, but also experienced copying, re-writing, and experiencing transformation. For the artists of the kethoprak it self, this stucy can be used as a reference to develop the story of Saridin in order it can always meet the demands of the community for entertaining people.